2007
DOI: 10.1210/en.2006-0793
|View full text |Cite
|
Sign up to set email alerts
|

An Orally Active Selective Androgen Receptor Modulator Is Efficacious on Bone, Muscle, and Sex Function with Reduced Impact on Prostate

Abstract: A number of conditions, including osteoporosis, frailty, and sexual dysfunction in both men and women have been improved using androgens. However, androgens are not widely used for these indications because of the side effects associated with these drugs. We describe an androgen receptor (AR) ligand that maintains expected anabolic activities with substantially diminished activity in the prostate. LGD2226 is a nonsteroidal, nonaromatizable, highly selective ligand for the AR, exhibiting virtually no affinity f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
85
0
4

Year Published

2007
2007
2013
2013

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 129 publications
(92 citation statements)
references
References 50 publications
2
85
0
4
Order By: Relevance
“…3a) were more likely to be tissue-selective. These data support the concept that partial agonism is a reliable, if imperfect, predictor of tissue selectivity, consistent with previous SARM discovery strategies (12)(13)(14)(15)(16)(17)(18)(19)32).…”
Section: Gene Regulation Endpoints As Biomarkers For the Actions Of Asupporting
confidence: 89%
See 1 more Smart Citation
“…3a) were more likely to be tissue-selective. These data support the concept that partial agonism is a reliable, if imperfect, predictor of tissue selectivity, consistent with previous SARM discovery strategies (12)(13)(14)(15)(16)(17)(18)(19)32).…”
Section: Gene Regulation Endpoints As Biomarkers For the Actions Of Asupporting
confidence: 89%
“…Raloxifene, for example, is a clinically used selective estrogen receptor modulator that slows bone loss and antagonizes estrogen actions in uterus and breast and reduces the risk of the devel-opment of estrogen receptor-dependent breast cancers (10,11). Preclinical proof of concept for an anabolic SARM with reduced androgenization was established in animal models by several SARMs such as TZP-4238, S-40503, S-1, S-4, LGD2226, LGD2941, JNJ-28330835, and JNJ-37654032 (12)(13)(14)(15)(16)(17)(18)(19). We developed a proof-of-concept SARM, TFM-4AS-1, that increases periosteal bone formation, cortical bone mass, and lean body mass as effectively as DHT but with markedly reduced effects on uterus, prostate, and the pilosebaceous unit (PSU) (20).…”
mentioning
confidence: 99%
“…Most SARMs show their selectivity according to the difference between the effects on the prostate (virilizing effect) and that on bone volume or muscle weights (anabolic effect). [13][14][15][16]22,[29][30][31] The reduced virilizing effect that was evaluated by the effect on the prostate is not sufficient to enable treatment for women who require diminished anabolic effects on the uterus. Recently, Merck Research Laboratories demonstrated the effects of bone-selective SARMs in a female animal model 32,33) ; different tissue selectivities are needed to develop postmenopausal osteoporosis drugs.…”
Section: Discussionmentioning
confidence: 99%
“…[9][10][11][12] Recently, the actions of non-steroidal selective androgen receptor modulators (SARMs) have been investigated in many laboratories. [13][14][15][16][17] Typically, they were observed to be more tissue-selective than anabolic steroids and were orally available in preclinical models. We have focused on bone anabolic SARMs to develop anti-osteoporosis agents without serious virilizing effects.…”
mentioning
confidence: 99%
“…Problem ve}ine SARM-ova bio je nezadovoljavaju}e razdvajanje njihova u~inka na kost i prostatu (46,47). Ipak, nedavna studija na `ivotinjskom modelu pokazala je da visokoselektivni SARM, LGD2226, inhibira resorpciju spu`vaste kosti a poti~e stvaranje kortikalne kosti, {to rezulira pove}anjem ~vrsto}e kosti (48). Istodobno, u usporedbi s testosteronom, rast prostate je bio zna~ajno manji u `ivotinja koje su dobivale LGD2226 (48).…”
Section: Fiziologija Kostiunclassified